Transition of Roles Change of Motherhood in Women - Yulizawati Yulizawati; Yantri Maputra; Iney Pive Enosentris (Journal of Midwifery, 2021)
Being a mother is an extraordinary experience for women. The transition to changing the role of being a mother is a process that a mother must go through in achieving her maternal identity. The purpose of this paper is to determine the transition from changing the role of being a mother to women. This type of writing is a narrative literature review, conducted in June-November 2020. Data was collected through the PubMed digital library, Science Direct and Google Scholar using inclusion and exclusion criteria. The data analysis was done qualitatively. The analysis was carried out on 19 research articles. The results of the paper show three main themes, namely motherhood, transition to motherhood in working and unemployed mothers, and the role of midwives in supporting the role transition process. The transition process of changing the role of motherhood to both working and non-working mothers, namely experiencing feelings of inadequacy, feeling alone, losing, then being able to realize, make adjustments and perform these roles. Midwives must provide care according to client needs